Cognitive worry in cognitively normal older adults is associated with decreased memory binding, hippocampal volume and parahippocampal thickness: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Markova, Hana; Mazancova, Adela Fendrych; Cechova, Katerina; Nikolai, Tomas; Matuskova, Veronika; Nedelska, Zuzana; Sheardova, Katerina; Laczó, Jan; Hort, Jakub; Vyhnalek, Martin
Abstract: Background: Worry associated with subjective cognitive decline (cognitive worry) in cognitively normal (CN) older adults has been established as a feature that increases the likelihood of preclinical Alzheimer´s disease (AD). Previously, it has been associated with a higher risk of progression to mild cognitive impairment and dementia. We aimed to examine whether presence of cognitive worry reflects poorer memory performance and decreased volumes or cortical thicknesses in AD‐related regions in CN older adults. Method: In total, 85 CN older adults reporting cognitive complaints were recruited from the Czech Brain Aging Study and classified into two groups by subjective evaluation of presence/absence of cognitive worry (WORRY+/‐, n = 36 and n = 49, respectively). All participants underwent a comprehensive neuropsychological examination, including the Rey Auditory Verbal Learning Test (RAVLT), Logical Memory I (LM I) and the challenging Memory Binding Test (MBT). 1.5T MRI with T1‐weighted 3‐dimensional images and FreeSurfer 5.3. algorithm was used to measure left and right hippocampal volume (HVL, HVR ), left and right entorhinal and parahippocampal thickness (ERCL, ERCR, PHCL, PHCR ). Individuals with significant vascular‐related white matter hyperintensities were not included. A one‐way ANCOVA assessed the between‐groups differences, controlling for sex, age and education. Result: The WORRY+ did not differ from the WORRY‐ group in the RAVLT or LM I scores, but performed significantly lower in the MBT scores evaluating both free and cued recall in immediate and delayed conditions (ps ≤ 0.012). Consistently, the WORRY+ group had significantly decreased adjusted HVR, decreased PHCL and PHCR (ps ≤ 0.019). No other between‐group differences were found in medial temporal lobe measures. Conclusion: Cognitive worry in CN older adults is associated with both poorer memory performance in the challenging test of memory binding and decreased hippocampal volume and parahippocampal thickness even cross‐sectionally. Given that cortical thinning and hippocampal atrophy on MRI, together with poor cognitive performance on challenging tests, are detectable in late stages of preclinical AD, cognitive worry may be a risk factor for imminent functional impairment and disease progression.